2020
DOI: 10.2174/0929867325666180514110824
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Treatment of Explicit Water Molecules in Docking and Binding Free Energy Calculations

Abstract: Software applications aiding the design of new drugs that exploit water molecules, either as displaceable residues or as bridges to the receptor, are constantly being developed. Although further validation is needed, workflows that explicitly consider water will probably become a standard for computational drug discovery soon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 240 publications
(293 reference statements)
0
21
0
Order By: Relevance
“…Thus, the abundant possibilities in the water arrangement prohibit a feasible, explicit evaluation of all the potential water interactions. The current state of how the water can be treated explicitly in docking is reviewed in [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the abundant possibilities in the water arrangement prohibit a feasible, explicit evaluation of all the potential water interactions. The current state of how the water can be treated explicitly in docking is reviewed in [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution from each residue of the TDP‐43 protein to the binding energy was calculated using molecular mechanics/generalized Born surface area (MM‐GBSA) decomposition protocol within the MMPBSA.py module 40–44 . The reason for choosing MM‐GBSA to decompose energy is because it saves time than MM‐PBSA 44 .…”
Section: Methodsmentioning
confidence: 99%
“…The contribution from each residue of the TDP-43 protein to the binding energy was calculated using molecular mechanics/generalized Born surface area (MM-GBSA) decomposition protocol within the MMPBSA.py module. [40][41][42][43][44] The reason for choosing MM-GBSA to decompose energy is because it saves time than MM-PBSA. 44 For the decompositions of MM-GBSA free energy calculations, the total binding free energy of each residue was decomposed into four contributions from the individual residue-residue pairs, including van der Waals interaction (E vdw ), electrostatic interaction (E ele ), polar solvation free energy (G pb ) and non-polar solvation free energy (G np ), respectively:…”
Section: Binding Free Energy Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Docking protocols have been developed to account for water molecules during ligand pose and affinity prediction, with mixed degrees of success, and these methods also inherit the difficulties and limitations typically associated with docking. 85 Many other methods have also been applied prospectively in live drug design, 20,41,165,166 though it is difficult to determine the contribution of the water analysis method to the design strategy, and it has been suggested that many compound modifications suggested would likely have been proposed by medicinal chemists using other structure-based design techniques. 41 It is important that more diverse methods are developed with the aim of forming more direct links between water molecules and ligand structureactivity relationships, to maximise utility in drug discovery and compound development.…”
Section: Application To Compound Designmentioning
confidence: 99%